2001
DOI: 10.1177/14034948010290010601
|View full text |Cite
|
Sign up to set email alerts
|

Self-rated health as a predictor of mortality among persons with cardiovascular disease in Sweden

Abstract: This study shows that subjective health ratings are important predictors of mortality for persons with cardiovascular disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
39
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 43 publications
1
39
0
1
Order By: Relevance
“…However, the relationship between (changes in) SRH and mortality risk among younger persons has not previously been examined, and our results may indicate that elderly persons may better sense if they are about to become ill/die. In a Swedish study a health decline among 60-to 67-year-old men increased the mortality risk [9]; a similar result was found in a 12-year follow-up study of elderly Swedish twins [12]: those with ''declined'' SRH after six years were more likely to die than those with ''unchanged good'' SRH. A cohort study on SRH patterns before significant medical events among elderly Americans, followed half-yearly for eight years, demonstrated that SRH gradually decreased five years preceding death [11].…”
Section: Relation To Other Studiesmentioning
confidence: 60%
See 2 more Smart Citations
“…However, the relationship between (changes in) SRH and mortality risk among younger persons has not previously been examined, and our results may indicate that elderly persons may better sense if they are about to become ill/die. In a Swedish study a health decline among 60-to 67-year-old men increased the mortality risk [9]; a similar result was found in a 12-year follow-up study of elderly Swedish twins [12]: those with ''declined'' SRH after six years were more likely to die than those with ''unchanged good'' SRH. A cohort study on SRH patterns before significant medical events among elderly Americans, followed half-yearly for eight years, demonstrated that SRH gradually decreased five years preceding death [11].…”
Section: Relation To Other Studiesmentioning
confidence: 60%
“…Among participants without chronic illness, ''unchanged poor'' indicated a decreased risk at all age-intervals although having declined or improved SRH gave a relatively high risk. Only two studies, including elderly persons, have reported on the relationship (not stratified for chronic illness) between ''unchanged poor'' SRH and mortality: one found an unchanged [9], the other an increased mortality risk [12]. Generally, ''unchanged poor'' SRH carries an increased mortality risk, but the group who rate their health as poor may comprise both health pessimists and persons with actual ''poor'' health [25], which is illustrated by the analysis among those without and with chronic illness.…”
Section: Relation To Other Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Similar associations have also been observed in patients with type 2 diabetes 12,13 and in patients with CVD. 14,15 However, the prognostic importance of QoL assessments in patients with both type 2 diabetes and CVD is less well investigated. The aim of the present investigation, a predefined sub-study of the DIGAMI 2 trial, was to test the hypothesis that self-related health and psychological well-being contribute with prognostic information of patients with type 2 diabetes and acute myocardial infarction (AMI).…”
Section: Introductionmentioning
confidence: 99%
“…It is frequently used as an end-point but a large number of studies have demonstrated that a person's own appraisal of her/his health is a powerful predictor of future morbidity (Segovia et al 1989;Bjorner et al 1996;Kaplan et al 1996;Moller et al 1996;Huibers et al 2004b) and mortality (Bjorner et al 1996;Idler and Benyamini 1997;Benyamini and Idler 1999;Bardage et al 2001;Burstrom and Fredlund 2001;Heidrich et al 2002;Larsson et al 2002;Af Sillén et al 2005;Vuorisalmi et al 2005). SRH is considered a cheap and convenient way of identifying risk groups and risk factors (Bjorner et al 1996), useful not least in working life.…”
Section: Introductionmentioning
confidence: 99%